Discovery of a new species of Formosatettix Tinkham, 1937 (Orthoptera, Tetrigoidea, Tetrigidae) from China - Zheng, Fang-Qiang; Shi, Jianping; Yin, Zhan (Zootaxa, 2015)
A new species of the genus Formosatettix Tinkham, 1937, namely Formosatettix xiai sp. n. is described and illustrated. The new species is allied to Formosatettix wulaoshanensis Zheng & Xu, 2010, but differs from the latter by the apex of pronotum reaching distal 2/3 of hind femur, width of frontal ridge equal to that of basal segment of antennae, length of a segment of antennae in the middle 3 times its width, lower margin of fore and mid femora straight, pronotum dorsally with one black spot on each side. The new species is also allied to Formosatettix tianmushanensis Zheng & Li, 2001, but the apex of pronotum reaching distal 2/3 of hind femur, the width of frontal ridge equal to that of basal antennal segment, length of upper ovipositor valve 3 times its width, length of a segment in the middle of antennae 5.0 times its width and pronotum dorsally with one black spot on each side. The type specimens are deposited in the College of Life Sciences, Hebei University, Baoding, Hebei, China.